Re-evaluating the potential impact and cost-effectiveness of rotavirus vaccination in 73 Gavi countries: a modelling study - Frédéric Debellut, MSc; Andrew Clark, PhD; Clint Pecenka, PhD; Jacqueline Tate, PhD; Ranju Baral, PhD; Colin Sanderson, ProfPhD; Umesh Parashar, MD; Laura Kallen, MPH; Deborah Atherly, PhD (Elsevier, 2019)
Summary: Background: Previous studies have found rotavirus vaccination to be highly cost-effective in low-income countries. However, updated evidence is now available for several inputs (ie, rotavirus disease mortality rates, rotavirus age distributions, vaccine timeliness, and vaccine efficacy by duration of follow-up), new rotavirus vaccines have entered the market, vaccine prices have decreased, and cost-effectiveness thresholds have been re-examined. We aimed to provide updated cost-effectiveness estimates to inform national decisions about the new introduction and current use of rotavirus vaccines in Gavi countries. Methods: We calculated the potential costs and effects of rotavirus vaccination for ten successive birth cohorts in 73 countries previously and currently eligible for Gavi support, compared with no vaccination. We used a deterministic cohort model to calculate numbers of rotavirus gastroenteritis cases, outpatient visits, hospitalisations, and deaths between birth and 5 years, with and without rotavirus vaccination. We calculated treatment costs from the government and societal perspectives. The primary outcome measure was the incremental cost-effectiveness ratio (discounted US$ per disability-adjusted life-year averted). Country-specific model input parameters were based on the scientific literature, published meta-analyses, and international databases. We ran deterministic and probabilistic uncertainty analyses. Findings: Over the period 2018-27, rotavirus vaccination has the potential to prevent nearly 600 000 deaths in Gavi countries. Averted outpatient visits and hospitalisations could lead to treatment savings of approximately $484·1 million from the government perspective and $878·0 million from the societal perspective. The discounted dollars per disability-adjusted life-year averted has a very high probability (>90%) of being less than 0·5 times the gross domestic product per capita in 54 countries, and less than 1·0 times gross domestic product per capita in 63 countries. Interpretation: Rotavirus vaccination continues to represent good value for money across most Gavi countries despite lower rotavirus mortality estimates and more stringent willingness-to-pay thresholds. Funding: Bill & Melinda Gates Foundation.